MENGGUNAKAN RICE COOKER MELALUI METODE DEMONSTRASI BAGI ANAK TUNAGRAHITA RINGAN (Single Subject Research di SLB Kasih Ummi Padang ) - Resa - Silvia (Universitas Negeri Padang, 2014)
This research found a backdrop of mild mental retardation eighth grade student in SLB Kasih Ummi Padang, have not been able to cook rice using a rice cooker. to improve the skills of cooking rice using a rice cooker, researchers aim to use methods of demonstration. based on these problems, the research aims to prove whether the method can improve the skills demonstration using a rice cooker to cook rice in class VIII in SLB Kasih Ummi Padang.